Situational and dispositional goals as predictors of perceptions of individual and team improvement, satisfaction and coach ratings among elite female handball teams - Balaguer, I.; Duda, J. L.; Atienza, F. L.; Mayo, C. (Psychology of Sport and Exercise, 2002)
Objectives. To examine the relationship of the perceived motivational climate created by the coach and dispositional goal orientations of elite female handball players¡¦ (a) perceived individual and team improvement in different facets of the game; (b) satisfaction with their own and the team¡¦s game; and (c) ratings of the coach. A second aim was to study whether the dependent variables were best predicted by the perceived motivational climate created by the coach and/or the players¡¦ dispositional goal orientations. Design. Cross-sectional. Methods: Elite female handball players (n=181) from 14 teams participating in a national handball competition in Spain completed the Spanish measures of goal orientations and climate and items assessing the dependent variables of interest. Results: When a stronger task-involving climate was perceived, players reported greater performance improvement and satisfaction with performance and held more positive views regarding the coach. Task orientation added a significant proportion of the variance for perceptions of one¡¦s own performance improvement. Perceptions of an ego-involving climate were negatively related to overall coach ratings but were positively related to satisfaction with the team¡¦s competitive results. Conclusions: The findings are consistent with the tenets of achievement goal theory and provide evidence for the adaptive implications of a task-involving climate in high-level sport. The superior predictive ability of climate over individual goals suggests that interventions targeted at the coach should have an important impact on individual and team motivation.